2008
DOI: 10.1016/j.habitatint.2007.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of homeownership in Malaysia

Abstract: The housing industry is crucial to the sustainable development in Malaysia. The efficiency and effectiveness of the housing delivery system requires housing provision for all. The housing industry, which had grown rapidly in the 1980s encountered property oversupply recently. The majority of these units remain unsold for reasons beyond price factor, ranging from poor location to unattractive houses. The main objective of this paper is to tackle property oversupply in the country by examining a detailed knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 16 publications
2
71
0
Order By: Relevance
“…However, Tan (2008) showed that employees from publicly-owned organizations consider ownership of a home as an investment tool for wealth accumulation. Tan (2008) further argued that employees from publicly-owned organizations are motivated to improve the quality of the neighborhood by holding a leading position in the local community organization as their working hours are fixed and predictable. High involvement in local politics may increase the propensity to own.…”
Section: Social Demographic Characteristics Of Respondentsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Tan (2008) showed that employees from publicly-owned organizations consider ownership of a home as an investment tool for wealth accumulation. Tan (2008) further argued that employees from publicly-owned organizations are motivated to improve the quality of the neighborhood by holding a leading position in the local community organization as their working hours are fixed and predictable. High involvement in local politics may increase the propensity to own.…”
Section: Social Demographic Characteristics Of Respondentsmentioning
confidence: 99%
“…Having a house has always been part of the Malaysian dream (Tan, 2008). In recent times, however, it has been a stretch for the average Malaysian to own a home.…”
Section: Introductionmentioning
confidence: 99%
“…Normally, people in the lowest income bracket are likely to opt for apartments (Opoku & Abdul-Muhmin 2010). Tan (2008) households as it indicates investors' capability to afford property and other assets. Higher income tends to influence the mobility of households as higher income clearly widens the likelihood of moving into larger and better houses (Tan, 2008).…”
Section: Disposable Income Of Investorsmentioning
confidence: 99%
“…Tan (2008) households as it indicates investors' capability to afford property and other assets. Higher income tends to influence the mobility of households as higher income clearly widens the likelihood of moving into larger and better houses (Tan, 2008). Shuid (2004) managed to express some concern on the low medium income in Kuala Lumpur's population with a percentage of 20.5%.…”
Section: Disposable Income Of Investorsmentioning
confidence: 99%
“…While it would be interesting to see how demographics such as age and income affect home ownership, limited data prevents competition of this study against more through analyses such as in Tan [27].…”
Section: Respondent Demographics and Home Ownershipmentioning
confidence: 99%